Effects of Team-Based Learning on short-term and long-term retention of factual knowledge*. (3rd March 2016) - Emke, Amanda R.; Butler, Andrew C.; Larsen, Douglas P.
Abstract: Purpose : We investigated the effect of Team-Based Learning (TBL) on long-term retention of knowledge in comparison to a traditional curriculum. Methods : As TBL was incorporated into our curriculum in the 2008–2009 academic year, students were compared with those who received the traditional curriculum the year prior. Students in both the groups completed multiple-choice knowledge test at four time points spanning two years. Test performance was compared at each time point to assess changes in knowledge retention as a function of time. Results : Baseline knowledge did not differ significantly between the TBL and control groups [51% versus 46%; t (84) = 0.91, p  = 0.37, d  = 0.20]. Performance improved after the course for both the groups, but was significantly higher in the TBL group [79% versus 59%; t (84) = 4.96, p  = 0.000004, d  = 0.95]. However, when assessed prior to the pediatrics clerkship, learning gains from TBL had largely disappeared and the small difference in performance was not significant [57% versus 51%; t (84) = 1.51, p  = 0.14, d  = 0.32]. Conclusion : Incorporating TBL into the pre-clinical pediatrics curriculum led to large gains in knowledge over the short-term, but these gains did not persist. Further research should focus on extending the impact of TBL on long-term knowledge retention.